Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015): International Conference, 1–4 December 2015, Tomsk, Russia; [proceedings]; IOP Conference Series: Materials Science and Engineering (2016, 2016)
Title screen